2019
DOI: 10.1002/lary.28335
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction in Academic Otolaryngology: Do Physician Demographics Impact Press Ganey Survey Scores?

Abstract: Objectives/Hypothesis Patient satisfaction is increasingly emphasized and measured in healthcare delivery. However, patient satisfaction is multifactorial and difficult to comprehensively assess. The objective of this study was to assess for correlation between patient satisfaction measured by Press Ganey surveys (PGS) and physician demographics of gender, years in practice, academic rank, and specialty in academic otolaryngology. Study Design Review of publicly available PGS scores in academic otolaryngology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Consistent with the findings in a similar study by Tracy et al, we did not find significant associations between PSS and provider gender or credentials 26 . Though Tracy et al found a weakly statistically significant decrease in mean scores was associated with longer duration of practice, we did not find a significant association between PSS and provider years of experience.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with the findings in a similar study by Tracy et al, we did not find significant associations between PSS and provider gender or credentials 26 . Though Tracy et al found a weakly statistically significant decrease in mean scores was associated with longer duration of practice, we did not find a significant association between PSS and provider years of experience.…”
Section: Discussionsupporting
confidence: 87%
“…As a matter of fact, patients' gender preference may differ depending on subspecialty; for example, head and neck oncology patients prefer males, while females are more preferred in pediatric otolaryngology [18]. On contrary, potential impact of physician's gender on patients' preference is not demonstrated in a study by Tracy LF et al [19].…”
Section: Discussionmentioning
confidence: 96%
“…Patient and family satisfaction is key to evaluating the quality of care, reimbursement, and certification requirements in all fields, including otolaryngology 1,4–6 . Although research examining family satisfaction in otolaryngology is increasing, most studies have focused on how differences in provider demographics, specialty, practice setting, as well as patient age and disease‐specific measures, affect satisfaction 4,7–10 . In otolaryngology, there is little research examining the intersection of health equity and family experience 11, 12 …”
Section: Introductionmentioning
confidence: 99%